Across establishments, within firms: worker's mobility, knowledge transfer and survival - Marisa Fernanda Figueiredo Tavares (Journal for Labour Market Research, 2020)
We analyze the recruitment strategies and the survival of newly created establishments that are affiliated with pre-established _rms. For the new establishments, the existence of ports of entry as well as the importance of internal and external recruitment is assessed. Being affiliated with a pre-established firm may be a source of competitive advantage and improve the new plant's chances of survival as the parent firm may supply the newly created unit with expertise and firm-specific knowledge. In this research we suggest a channel for knowledge transfer that has been little addressed in previous literature: within firm and across establishments mobility of workers. As firm-specific knowledge is mainly embodied and non-tradable, we suggest that it can be successfully transferred to the new unit embodied in the workers that are internally recruited. We find that internally transferred workers, particularly skilled workers hired at high-rank jobs play an important role in improving the survival of new establishments.
Keywords: J61; J62; L25; 330; Worker's mobility; Knowledge transfer; New establishment's survival